Pengaruh Katarsis Emosi Terhadap Perilaku Anonim Pada Remaja di SMANegeri 1 Tondano Pengguna Media Sosial - Andrea Angelita Kusen; Deetje Josephine Solang; Rinna Yuanita Kasenda (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study examines the influence of emotional catharsis on anonymous behavior among adolescent Social Media Users at SMA Negeri 1 Tondano. Utilizing a quantitative approach, the research employs a simple linear regression analysis. Using purposive sampling, 155 participants from grades XI and XII who actively use social media were selected. Data were gathered through questionnaires. The findings reveal a p-value of 0.000 (p < 0.05), indicating that emotional catharsis has a significant impact on anonymous behavior among adolescent social media users at SMA Negeri 1 Tondano.